Eon : Dragoneye reborn / 1. - Goodman, Alison (Eon, 2008)
Sixteen-year-old Eon hopes to become an apprentice to one of the twelve energy dragons of good fortune and learn to be its main interpreter, but to do so will require much, including keeping secret that she is a girl.